Migránsok, menekülők, szerencsét próbálók és társaik. I. rész - Dövényi, Zoltán (Közép-Európai Közlemények, 2016)
Undoubtedly, 2015 was the year of migration in Europe: much more than one million people arrived to the „old continent” from not european contries – most of them without registration and authority controll. The questions and problems emerged in this study refer to this massive migration:1. Why 2015 was the very year, when migrants started to get going? We can specify more reasons (which are connected or build on each other)• Syrian war consists.•The Balkan migration corridor opened.• Turkey’s languidity in stop of migration.• Greek’s poor performance in reception of migrants adequately to EU regulations.• Germany’ inviting behaviour to syrian migrants.2. Who arrived and what do they want? As registration of migrants are very defective, we hardly have reliable information about these people.Sure:• Men are overrepresented.• Young age groups (< 30 years) make the major part of migrants.• Yearly sure:• In the case of the most migrants educational achivement is low.• Fast labour market integration of them is very doubtful.